PENINGKATAN KUALITAS LAYANAN KEPERAWATAN SECARA LANGSUNG MELALUI APLIKASI NIC-NOC TERPADU - Andi Eka pranata; Said Mardjanto (Jurnal Kesehatan dr. Soebandi, 2018)
The quality of nursing services is reflected by the comprehensive, holistic nursing care activities which meet the nursing standards. Often, the facts show that the quality of the nursing services is below expectation as demonstrated by the documentation proof which is non-standard, thus affects the outcome of the service itself. The objective of this research is to find out the effect of the use of integrated NIC-NOC application on the direct improvement of the nursing services quality at the outpatient treatment room at Rambipuji Primary Health Jember Regency. This research employs one group pretest-postest design by using quasi experiment design. This research is conducted at the outpatient treatment room of Rambipuji Primary Health Jember Regency by involving the patient as the sample of the research. The result of this research reveals that the use of integrated NIC-NOC application proves to improve the quality of the nursing services as reflected by 4 domains, namely: satisfaction level, relevance level, continuity level, as well as evidence level, respectively.